2021
DOI: 10.1016/j.isci.2021.102391
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic tolerance, persistence, and resistance of the evolved minimal cell, Mycoplasma mycoides JCVI-Syn3B

Abstract: Summary Antibiotic resistance is a growing problem, but bacteria can evade antibiotic treatment via tolerance and persistence. Antibiotic persisters are a small subpopulation of bacteria that tolerate antibiotics due to a physiologically dormant state. Hence, persistence is considered a major contributor to the evolution of antibiotic-resistant and relapsing infections. Here, we used the synthetically developed minimal cell Mycoplasma mycoides JCVI-Syn3B to examine essential m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 101 publications
0
17
0
Order By: Relevance
“…We did a similar FT with clones grown from a single cell and treated them with a lethal Amp concentration (0.1 mg/mL). % Survival was determined for 1 h and 3 h of treatment using persister assays 26,27,34 , and short-term tolerance at 1 h does not indicate the level of persistence at 3 h with lethal Amp; no correlation at 1 h vs 3 h population (r 2 = 0.02). If the primed cells are advantageous for long-term survival, we expect the high persister populations observed at 3 h treatment to stay high with more prolonged antibiotic exposure.…”
Section: Resultsmentioning
confidence: 99%
“…We did a similar FT with clones grown from a single cell and treated them with a lethal Amp concentration (0.1 mg/mL). % Survival was determined for 1 h and 3 h of treatment using persister assays 26,27,34 , and short-term tolerance at 1 h does not indicate the level of persistence at 3 h with lethal Amp; no correlation at 1 h vs 3 h population (r 2 = 0.02). If the primed cells are advantageous for long-term survival, we expect the high persister populations observed at 3 h treatment to stay high with more prolonged antibiotic exposure.…”
Section: Resultsmentioning
confidence: 99%
“…We did a similar FT with clones grown from a single cell and treated them with a lethal Amp concentration (0.1 mg/mL). % Survival was determined for 1 h and 3 h of treatment using persister assays 26, 27, 34 , and short-term tolerance at 1 h does not indicate the level of persistence at 3 h with lethal Amp; no correlation at 1 h vs 3 h population (r 2 = 0.02). If the primed cells are advantageous for long-term survival, we expect the high persister populations observed at 3 h treatment to stay high with more prolonged antibiotic exposure.…”
Section: Resultsmentioning
confidence: 99%
“…neoformans, the results of this study showed that Fluc-O2ME-NP outperformed free Fluc at both tested pH conditions, especially at pH 5. Fungal cells incubated with Fluc alone, even at the highest tested drug concentration of 175 μg/mL, demonstrated a plateau behavior indicating antifungal resistance with a cell density of around 10–25% persisting from 10 to 24 h with no indication of fungal cell populations reducing . On the contrary, C.…”
Section: Discussionmentioning
confidence: 96%